PENGARUH INTELLECTUAL CAPITAL, KEPEMILIKAN INSTITUSIONAL DAN KEPEMILIKAN MANAJERIAL TERHADAP KINERJA KEUANGAN PERUSAHAAN: (Studi Kasus : Perusahaan Manufaktur Consumer Non-Cyclical yang Terdaftar Di BEI Tahun 2019-2021) - Eufrasia Ogi Danta Putri; Yulia Setyarini (J-MACC, 2024)
The development and globalization of technology, marked by a shift in technology from the era of hard automation to the era of smart technology, therefore intangible assets are very important. Therefore, companies are increasingly focusing on knowledge assets. One of the approaches used to assess and measure knowledge assets is Intellectual Capital (IC). In order for the main goals of the company to be achieved, the company gives authority to managers to manage the company properly. However, if it is only given to one party, then that party will tend to seek benefits for himself. So that it is necessary to have an oversight of the management without adding to the agency cost with ownership by other institutions, namely institutional ownership. The method used in this study is to use the VAIC formula to calculate intellectual capital, the institutional ownership ratio formula, and the managerial ownership ratio, as well as the ROA formula to calculate a company's financial performance. The research object chosen is a non-cyclical consumer manufacturing company because this company is not affected by economic growth so that the results can focus on the variables studied, that is intellectual capital (X1), Institutional Ownership (X2), and Managerial Ownership (X3). The results of this study indicate (1) intellectual capital has an effect on the financial performance of manufacturing companies, (2) institutional ownership have no effect on financial performance of manufacturing companies, (3) managerial ownership have no effect on financial performance of manufacturing companies.